Neurociência cognitiva organizacional e suas aplicações no ambiente de trabalho: uma análise sobre a percepção dos líderes - Duarte, Heriton Mascarelo (Universidade do Vale do Rio dos Sinos, 2020)
This paper analyzes the perception of leaders about the discoveries of organizational cognitive neuroscience (NCO) and their practical applications in the work environment, as well as identifying gaps and distortions of knowledge that leaders have about this area of study, which seeks to fundamentally understand the dynamics between the functioning of the brain at the neurological level and the reflexes on the behavior of individuals in organizational environments. Based on a study with the participation of one hundred and thirty-six respondents, of which part consider themselves in leadership positions, conducted in two stages, using a quantitative and qualitative method, it was possible to highlight the perception of such leaders about the practices currently used in their companies, even though they are unaware of the neurological factors and reflexes that trigger them. The results also made it possible to propose initiatives and actions for leaders regarding the expansion of knowledge about NCO. Finally, this research presents recommendations for including or changing internal and external leadership training programs on the topics covered in Organizational Cognitive Neuroscience.
Keywords: Neurociência organizacional; Neurociência cognitiva organizacional; Gestão de pessoas; Gestão; Comportamento organizacional; Neurociência; Liderança organizacional; Organizational neuroscience; Organizational cognitive neuroscience; People management; Management; Organizational behavior; Neuroscience; Organizational leadership; ACCNPQ::Ciências Sociais Aplicadas::Administração